Spatial distribution and habitat characteristics of Macadamia hildebrandii in the Sintuwu Maroso Protection Forest, Central Sulawesi, Indonesia - Akhbar; SITI NURYANTI; NAHARUDDIN (Society for Indonesian Biodiversity, 2020)
Abstract. Akhbar, Nuryanti S, Naharuddin. 2020. Spatial distrubution and habitat characteristics of Macadamia hildebrandii in the Sintuwu Maroso Protection Forest, Central Sulawesi, Indonesia. Biodiversitas 21: 770-779. Research on the spatial distribution of Macadamia hildebrandii Steen (haleka) tree species is one of the important stages in the preservation of Sulawesi's endemic plants. The purpose of this research was to obtain information regarding the spatial distribution of M. hildebrandii in the area of Sintuwu Maroso Forest Management Unit, Central Sulawesi and the relationship between its occurrence with habitat characteristics in term of land and climate variables. Data was collected by establishing sampling plots using stratified systematic sampling based on land cover, namely primary and secondary dryland forests. Index of dispersion was used to calculate the distance between population while the chi-square test was used to investigate the relationship between M. hildebrandii population and variables of land and climate. The results showed that the M. hildebrandii trees mostly grew in the mountain rain zone ecosystem, clumped in groups according to the characteristics of the dominant natural habitat. The important characteristics of its habitat were it had red-yellow podzolic-lithosol soil type, altitude of ? 1,500 m asl, slope class of ? 25%, middle slope aspect, tineba volcano rock formation (which is volcanic sedimentary rocks), metamorphic parent material, secondary dryland forests, and rainfall of 1,600-2,000 mm/year. The results of study can be used as baseline information for the conservation and sustainable utilization, including cultivation, of M. hildebrandii especially in the montane zone of rain forest ecosystem in Sulawesi.